A hidden treasure along Silk Roads: An unexpected new species of spoon-winged lacewings from Xinjiang, China, and a revision of the genus Brevistoma Tjeder, 1967 (Neuroptera: Nemopteridae) - Zheng, Yuchen; Ni, Ziyang; Aspöck, Ulrike; Aspöck, Horst; Badano, Davide; Nel, André; Liu, Xingyue (Zootaxa, 2025)
Nemopteridae (spoon-winged or thread-winged lacewings) is a rare group in China, with significant value of conservation. Here, we report a new species of spoon-winged lacewing species, and the third known from China, namely Brevistoma raksasiae Zheng, Ni & Liu sp. nov. (Nemopteridae: Nemopterinae) from the Turpan Basin in Xinjiang. We also revise the genus Brevistoma Tjeder, 1967, providing redescription of three species: B. bardii (Navás, 1914), B. gallagheri Hölzel, 1999, and B. hackeri Hölzel, 1999. Additionally, we restore the validity of B. bourboni (Navás, 1931) stat. rev. The distribution of the new Brevistoma species is remarkable, as the species of this genus had been recorded in the Arabian Peninsula and North Africa. Our new finding highlights the uniqueness of the insect fauna of the Turpan Basin and its biogeographical connection with the Arabian Peninsula and North Africa.